KONSEP PEMIKIRAN PENDIDIKAN MENURUT PAULO FREIRE DAN KI HAJAR DEWANTORO - Syaikhudin, Ahmad (IAIN Ponorogo, 2012)
Abstract: Criticism and alternative education offered by Paulo Freire is very interesting to be used to analyze the problems of education in Indonesia. It must be admitted that the context behind the controversial issue of those educational thought is different from that of Indonesian, however, it must be very suitable. According to Paulo Freire, there should be no dichotomy between the goals of education and educational ways. The goal, the transformation that frees individual to be a real person, should be manifested in the extent to how education must be implemented. The purpose of exemption cannot be separated with the path that frees. In addition, Freires educational theory remains significant in terms of its role in which education should bring up not only the understanding of the world, but also the transformation of the world. On the other hands, Indonesian national leaders, Ki Hajar Dewantara also has inherited a very important philosophy in our national education, that is ing ngarso sung tulodo, ing madyo mangun karso, tut wuri handayani which means that the front is setting as a good model, the middle is inspiring and in the back provides support.